Pengaruh Ukuran Perusahaan, Ukuran Dewan Komisaris dan Pertumbuhan Perusahaan terhadap Pengungkapan Corporate Social Responsibility - Lestari, Widhian Ikka; Rusdi, Rusdi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Corporate Social Responsibility (CSR) disclosure has become increasingly important for mining companies in Indonesia, which often face environmental risks, social pressures, and financial challenges. Despite the growing attention, previous studies provide inconsistent findings on the determinants of CSR disclosure. This study aims to examine the effect of company size, board of commissioners’ size, and company growth on CSR disclosure among mining companies listed on the Indonesia Stock Exchange. The study employed purposive sampling, yielding 55 firm-year observations from 11 companies during the period 2019–2023. Secondary data were obtained from annual and sustainability reports, and panel data regression analysis was conducted using the fixed effect model with EViews 13. The results show that, simultaneously, company size, board of commissioners’ size, and company growth significantly influence CSR disclosure. Partially, company size has a positive and significant effect, while the size of the board of commissioners and company growth have no significant effect. These findings imply that larger firms tend to disclose more CSR activities to maintain legitimacy and stakeholder trust, whereas company growth and board structure do not guarantee broader CSR disclosure. The study contributes to the literature by providing updated evidence from the Indonesian mining sector and offers insights for managers and regulators in strengthening CSR practices.